2022
DOI: 10.1021/acs.jpcb.2c04615
|View full text |Cite
|
Sign up to set email alerts
|

Design of Peptides for Membrane Insertion: The Critical Role of Charge Separation

Abstract: A physical understanding of membrane permeation and translocation by small, positively charged molecules can illuminate cell penetrating peptide mechanisms of entry and inform drug design. We have previously investigated the permeation of the doubly charged peptide WKW and proposed a defect-assisted permeation mechanism where a small molecule with +2 charge can achieve a metastable state spanning the bilayer by forming a membrane defect with charges stabilized by phospholipid phosphate groups. Here, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Membranes are highly viscous fluids with strong interactions between their components and significant dynamic and static correlations. The findings of the formation of spatial and temporal microdomains in membranes demonstrate those correlations [ 10 , 11 , 49 , 51 , 52 ]. To examine correlations beyond pairs ( Figure 5 ) we plotted distributions of three body distances from the phospholipids to the center of mass of the peptide ( Figure 8 and Figure 9 ).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Membranes are highly viscous fluids with strong interactions between their components and significant dynamic and static correlations. The findings of the formation of spatial and temporal microdomains in membranes demonstrate those correlations [ 10 , 11 , 49 , 51 , 52 ]. To examine correlations beyond pairs ( Figure 5 ) we plotted distributions of three body distances from the phospholipids to the center of mass of the peptide ( Figure 8 and Figure 9 ).…”
Section: Resultsmentioning
confidence: 65%
“…The charges of the peptide (red spheres) remain close to the membrane surface. As we indicated in our previous studies [ 23 , 48 , 49 , 50 ], significant membrane distortions are required to allow the charges to pass the hydrophobic core and to switch to the other side of the membrane. These events did not occur in the relatively short simulations we conducted here.…”
Section: Resultsmentioning
confidence: 97%
“…On the basis of previous studies, it is likely that all three peptides are, to some extent, translocating from the exterior to the interior of LUVs on the time scale of our experiments. 15,36 If so, the peptides would be able to insert into both leaflets of the bilayer and, thus, should be impacted by the anionic lipid composition of both leaflets. This effect may explain the slight high-energy shift of R 6 W 3 and WWWK in LUVs with 10 mol % outer leaflet anionic lipid and 30 mol % inner leaflet anionic lipid compared to vesicles with 10 mol % anionic lipid in both leaflets, as the inner leaflet composition of the asymmetric LUV would promote insertion of translocated peptides back into the membrane.…”
mentioning
confidence: 99%
“…We have recently shown that permeants can traverse membranes through a defect-assisted mechanism in which a cationic peptide can cross the hydrophobic region of the bilayer by increasing membrane hydration and interacting with inner and outer leaflet lipid headgroups and phosphates. Furthermore, anionic lipids can affect CPP–membrane interactions and insertion in a headgroup-dependent manner. , A recent study from our group using an anticancer CPP, NAF-1 44–67 , showed that phosphatidic acid (PA) lipids enhanced membrane insertion and translocation to a greater extent than phosphatidylserine (PS) and phosphatidylglycerol (PG) lipids . Computational studies also suggest that this peptide permeates deeper in membranes with binary mixtures of PA or PS and zwitterionic phosphatidylcholine (PC) and locally enriches its environment with anionic lipids .…”
mentioning
confidence: 99%
See 1 more Smart Citation